The Fish Community Of The Tondano River Estuary In Manado City: - Dei, Katrin Dowena; Rondonuwu, Ari B.; Wantasen, Adnan S.; Mandagi, Stephanus; Mantiri, Rose O. S. E.; Kambey, Alex D. (Sam Ratulangi University, 2024)
This study was conducted to determine the relative abundance, species composition, relative abundance, and structure of fish communities. The data collection method used was the “Swept area” method. Sampling was conducted twice. The first sampling was conducted on June 17, 2023, and the second sampling was conducted on July 4, 2023, at the Tondano River estuary. Data collection was conducted at low tide. The data analysis used was relative abundance, diversity index, evenness index, and dominance index. The results of this study showed that the fish species composition in the Tondano River estuary consisted of 15 families, 15 genera, and 18 species with a total of 288 individuals. Between the two observed months, June and July, the number of species was higher in June. Based on the data analysis, the highest relative abundance in the Tondano River estuary was in the June phase, namely the Ambassis urotaenia species with a value of 31.5%. The diversity of fish species in the June and July phases was classified as quite high, considering the relatively high evenness index and low dominance index. Keywords: Tondano River Estuary, Relative Abundance, Diversity Index. Abstrak Penelitian ini dilakukan dengan tujuan untuk mengetahui kelimpahan relatif, komposisi spesies ikan, kelimpahan relatif dan struktur komunitas ikan. Metode pengambilan data ikan menggunakan metode metode “Swept area”. Pengambilan sampel dilakukan sebanyak 2 kali. Pengambilan sampel pertama dilakukan pada bulan juni tanggal 17 juni 2023 dan pengambilan sampel kedua dilakukan pada bulan juli tanggal 4 juli 2023 yang berlokasi di Muara Sungai Tondano. Pengambilan data dilakukan pada waktu surut. Analisis data yang digunakan adalah kelimpahan relatif, indeks keanekaragaman, indeks kemerataan, dan indeks dominansi. Hasil penelitian ini menunjukkan komposisi jenis ikan di Muara Sungai Tondano terdiri 15 famili, 15 genus dan 18 spesies dengan total 288 individu. Diantara kedua fase bulan yang diamati, yaitu bulan Juni dan bulan Juli, jumlah spesies lebih banyak ditemukan pada Juni. Berdasarkan hasil analisis data kelimpahan relatif tertinggi di Muara Sungai Tondano ada pada fase Juni yaitu spesies Ambassis urotaenia dengan nilai 31.5 %. Keanekaragaman jenis ikan pada fase bulan Juni dan Juli tergolong cukup tinggi dengan memperhatikan indeks kemerataan yang cukup tinggi dan indeks dominansi yang rendah. Kata kunci: Muara Sungai Tondano, Kelimpahan Relatif, Indeks Keanekaragaman.